Testing New Peptides From Toxoplasma gondii SAG1, GRA6, and GRA7 for Serotyping: Better Definition Using GRA6 in Mother/Newborns Pairs With Risk of Congenital Transmission in Mexico - Xicoténcatl-García, Lizbeth; Enriquez-Flores, Sergio; Correa, Dolores (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii variant influences clinical profile in human congenital and ocular toxoplasmosis. Parasite genotyping represents a challenge due to insufficient amount of genetic material of the protozoan in the host samples, and isolates are hard to obtain, especially from pediatric patients. An alternative is serotyping, which is based on the presence of specific antibodies against polymorphic proteins related to virulence; the more widely used are GRA6 and GRA7, but most works report cross reactions among the classical strains (I, II and III). We designed new peptides of GRA6, GRA7 and SAG1 proteins, with more SNPs among the three clonal strains than those previously designed. This was done by identifying BcR and polymorphic epitopes by means of bioinformatics; then we designed peptides with linkers joining the specific regions and predicted their 3D structure. With the commercial molecules synthesized on the basis of these designs, we tested 86 serum samples from 42 mother/newborn pairs and two congenitally infected newborns, by indirect ELISA. We implemented a strategy to determine the serotype based on scatter plots and a mathematical formula, using ratios among reactivity indexes to peptides. We found low frequency of samples reactive to GRA7 and SAG1, and cross reactions between GRA6 serotypes I and III; we modified these peptide types of GRA6, and largely improved distinction among the three clonal strains. The chronicity of the infection negatively affected the reactivity index against the peptides. Serotyping both members of the mother/child pair improves the test, i.e. in 26% of couples only one member was positive. Serotype I was the most frequent (38%), which was congruent with previous genotyping results in animals and humans of the same area. This serotype was significantly more frequent among mothers who transmitted the infection to their offspring than among non-transmitters (53% vs 8%, p=0.04) and related to disease dissemination in congenitally infected children, although non-significantly. In conclusion, serotyping using the improved GRA6 peptide triad is useful to serotype T. gondii in humans and could be implemented for clinical management and epidemiological studies to provide information on the parasite type in specific areas.